2021
DOI: 10.1155/2021/7029944
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antibiofilm Efficacy of Thymol and Piperine in Combination with Three Aminoglycoside Antibiotics against Klebsiella pneumoniae Biofilms

Abstract: Background. Thymol and piperine are two naturally occurring bioactive compounds with several pharmacological activities. In this study, their antibiofilm potential either alone or in combination with three aminoglycoside antibiotics was evaluated against a biofilm of Klebsiella pneumoniae. Methods. Determination of antimicrobial susceptibility was performed using the broth microdilution method. Biofilm formation was evaluated by the microtiter plate method. Antibiofilm activity was determined using 3-(4, 5-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Our results received for thymol are similar to those obtained by other authors. For example, Bisso Ndezo et al [ 30 ] analysed the effect of thymol against four strains of K. pneumoniae isolated from urine. The authors evaluated the MIC and MBC values of thymol against bacteria, which ranged from 0.064–0.256 mg/mL and 0.256–0.512 mg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our results received for thymol are similar to those obtained by other authors. For example, Bisso Ndezo et al [ 30 ] analysed the effect of thymol against four strains of K. pneumoniae isolated from urine. The authors evaluated the MIC and MBC values of thymol against bacteria, which ranged from 0.064–0.256 mg/mL and 0.256–0.512 mg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the kinetic metabolic activity of biofilm formation in a previous study [ 10 ], the biofilm biomass of K. pneumoniae isolates was determined with a colorimetric method based on safranin dye [ 21 ]. Briefly, 100 µ L of bacterial inoculum (1.5 × 10 6 CFU/mL) and 100 µ L of MHB supplemented with 2% glucose were added to a 96-well flat-bottomed polystyrene plate.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, thymol significantly inhibited 88% of methicillin-resistant Staphylococcus aureus (MRSA) biofilm formation at 100 μ g/mL, reduced the surface adherence of MRSA, and enhanced the antibacterial and biofilm eradication efficiency of rifampicin against MRSA [ 9 ]. In addition, our recent studies reported a synergistic antibiofilm effect between thymol and aminoglycosides against K. pneumoniae and Salmonella enterica biofilms [ 10 , 11 ]. The association of thymol with antibiotics showed a strong synergistic effect both in the inhibition of biofilm formation and the destruction of the preformed biofilm of K. pneumoniae , with the minimum biofilm inhibitory concentration (MBIC) and the minimum biofilm eradication concentration (MBEC) values of streptomycin being reduced by 16- to 64-fold [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations